Urgensi dan Substansi Permainan Bahasa dalam Pembelajaran Bahasa Arab - Mukhlis Anshari; M. Syamsuddin Noor (PT. Sharia Journal and Education Center, 2024)
Language games are various games that utilizing language as the main element. Three important elements in language games are: 1) something unique and interesting; 2) reward; 3) punishment. Language materials are divided into two, namely those related to language elements and those related to language skills. Creativity in making various language games is always wide open for teachers, not confined by the form, content, time duration, and method of play, but the creativity must still be adjusted to the conditions of the language. creativity must still be adapted to the appropriate learning conditions. appropriate learning conditions. Permainan bahasa adalah berbagai permainan yang memanfaatkan bahasa sebagai unsur utama. Tiga unsur penting dalam permainan bahasa adalah: 1) sesuatu yang unik dan menarik; 2) reward (hadiah); 3) punishment (hukuman). Materi bahasa terbagi dua yaitu yang terkait dengan unsur bahasa dan yang terkait dengan keterampilan berbahasa. Kreatifitas dalam membuat berbagai permainan bahasa selalu terbuka lebar bagi para pengajar, tidak terkungkung oleh bentuk, isi, durasi waktu, dan cara permainan, tetapi kreatifitas tersebut harus tetap disesuaikan dengan kondisi pembelajaran yang sesuai.